Unexpected Complications of Novel Deep Brain Stimulation Treatments: Ethical Issues and Clinical Recommendations. Issue 2 (30th May 2017) - Maslen, Hannah; Cheeran, Binith; Pugh, Jonathan; Pycroft, Laurie; Boccard, Sandra; Prangnell, Simon; Green, Alexander L.; FitzGerald, James; Savulescu, Julian; Aziz, Tipu
Abstract : Background: Innovative neurosurgical treatments present a number of known risks, the natures and probabilities of which can be adequately communicated to patients via the standard procedures governing obtaining informed consent. However, due to their novelty, these treatments also come with unknown risks, which require an augmented approach to obtaining informed consent. Objective: This paper aims to discuss and provide concrete procedural guidance on the ethical issues raised by serious unexpected complications of novel deep brain stimulation treatments. Approach: We illustrate our analysis using a case study of the unexpected development of recurrent stereotyped events in patients following the use of deep brain stimulation (DBS) to treat severe chronic pain. Examining these unexpected complications in light of medical ethical principles, we argue that serious complications of novel DBS treatments do not necessarily make it unethical to offer the intervention to eligible patients. However, the difficulty the clinician faces in determining whether the intervention is in the patient's best interests generates reasons to take extra steps to promote the autonomous decision making of these patients. Conclusion and recommendations: We conclude with clinical recommendations, including details of an augmented consent process for novel DBS treatment.